Association of Campylobacter jejuni with laying hens and eggs. - Doyle, M P (1984)
Laying hens were individually caged at 20 weeks of age and tested for fecal excretion of Campylobacter jejuni (minimum level of detection was 100 cfu/g) during a 42-week period. Peak rates of C. jejuni isolation (approximately 25% of hens positive) occurred at two different times, in October and in late April to early May. Before being segregated in late September, birds were allowed to consume fecal matter, litter, and communal drinking water, all likely sources of C. jejuni. The increased excretion rate in late April may have been due to a climatic change. A small portion (8.1%) of the hens chronically excreted (positive less than 30% of the sampling times) the organism, whereas C. jejuni was not detected in 33% of the hens, even though birds were likely exposed to the organism before being segregated. No correlation could be made between rates of C. jejuni excretion and egg production. Of 266 eggs from hens fecally excreting C. jejuni, the organism was isolated from two shell surfaces but no egg contents. Egg penetration studies revealed that the organism would not penetrate into the contents of the eggs but could be isolated occasionally from the inner shell and membranes of refrigerated eggs.